Incentivos tributarios como medio de aplicación a conductas medioambientales responsables en el cultivo de hortalizas, mellocos, raíces y tubérculos en la provincia de Chimborazo - Allauca Flores, Paulina Alexandra (2017)
The present research carries out a study on tax incentives as a means of application to responsible environmental behaviors in the cultivation of vegetables, mellocos, roots and tubers; Where the agrarian industry generates an adequate cultivation process with the purpose of determining the cost benefit of application of tax incentives, which generates a positive impact on the revenues of the State. It analyzes the legal environmental legislation that allows establishing appropriate procedures for the improvement of responsible environmental behavior in the crop, as well as the achievement of the ISO 14000 standard on Environmental Management Systems in agricultural enterprises. It also establishes a reform of the Internal Tax Regime Law specifically for income tax in order to encourage the use of safe environmental practices for a sustainable and sustainable development of Ecuador's agricultural sector.